علمِ حدیث میں علامہ انور شاہ کاشمیری کا منہج و استدلال (العرف الشذی کی روشنی میں) : Method & argument of Allama Anwar Shah Kashmiri in the light of Al-Arf al-Shadhi - Dr.Ahsan raza,; Dr. Umar Hayat, (MEI, 2024)
"The importance of the Prophetic word/ Hadith is an outstanding topic in Islamic studies being a basic source of Islamic teachings. In this way, the science of Hadith has its own significance and there is found a lot of excellent literature produced in this regard. Among the people who contributed in this field, the name of Anwar Shah Kashmiri is also included. He wrote a book entitled "العرف الشذی" in this regard, a unique one. In the following article, this book is focused analysing the methodology of argumentation of the author for the purpose of understanding the technicalities of the science of Hadith." Key words: the Prophetic word, Islamic studies, Science of Hadith, Anwar Shah Kashmiri, العرف الشذی